2017
DOI: 10.1038/nature23880
|View full text |Cite
|
Sign up to set email alerts
|

Competing memories of mitogen and p53 signalling control cell-cycle entry

Abstract: Regulation of cell proliferation is necessary for immune responses, tissue repair, and upkeep of organ function to maintain human health. When proliferating cells complete mitosis, a fraction of newly born daughter cells immediately enter the next cell cycle, while the remaining cells in the same population exit to a transient or persistent quiescent state. Whether this choice between two cell-cycle pathways is due to natural variability in mitogen signalling or other underlying causes is unknown. Here we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
232
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(252 citation statements)
references
References 27 publications
18
232
2
Order By: Relevance
“…We next introduced the DNA damaging agent neocarzinostatin (NCS) to mother cells and measured the phase durations for daughter cells (Fig J, Appendix Fig S9A). Recent work in human cells has shown that DNA damage signaling in the mother cell's G2 can persist through mitosis to lengthen the duration of G1, suggesting that coupling of maternal G2 and daughter G1 could potentially arise under genotoxic stress (Arora et al , ; Barr et al , ; Yang et al , ). As expected, at the highest NCS dosages that permitted cells to finish a cell cycle without permanent arrest, we confirmed that DNA damage significantly lengthened G1 in daughter cells (Fig K, Appendix Fig S8P).…”
Section: Resultsmentioning
confidence: 99%
“…We next introduced the DNA damaging agent neocarzinostatin (NCS) to mother cells and measured the phase durations for daughter cells (Fig J, Appendix Fig S9A). Recent work in human cells has shown that DNA damage signaling in the mother cell's G2 can persist through mitosis to lengthen the duration of G1, suggesting that coupling of maternal G2 and daughter G1 could potentially arise under genotoxic stress (Arora et al , ; Barr et al , ; Yang et al , ). As expected, at the highest NCS dosages that permitted cells to finish a cell cycle without permanent arrest, we confirmed that DNA damage significantly lengthened G1 in daughter cells (Fig K, Appendix Fig S8P).…”
Section: Resultsmentioning
confidence: 99%
“… Mammalian cells integrate mitogen and stress signaling prior to the end of G1 phase to decide whether or not to enter the cell cycle 14 . Before cells can replicate their DNA in S phase, they have to activate cyclin-dependent kinases (CDKs), induce an E2F transcription program, and inactivate an E3 ubiquitin ligase, the anaphase promoting complex/cyclosome (APC/C Cdh1 ).…”
mentioning
confidence: 99%
“…Variability in protein concentration due to stochasticity in gene expression, protein partitioning during cell division, stress signals, coupling to the circadian clock, and environmental changes have all been implicated in regulating the inherent variability in cell cycle phase durations in individual cells. On the other hand, recent work (Arora et al , ; Yang et al , ) has also shown that heritable factors from mother to daughter cells enable similarities in cell cycle phase dynamics between sister cells across cell lineages.…”
Section: Toy Model Proposing Uncoupling Between Cell Cycle Phase Duramentioning
confidence: 99%